RANCANGAN HANDOUT BIOLOGI PADA MATERI EKOSISTEM KELAS X SMA BERDASARKAN STRUKTUR KOMUNITAS PLANKTON DI SUNGAI KAMPAR KECAMATAN KOTO KAMPAR HULU RIAU - Rosita, Liyan; Yustina; Darmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Biology learning on ecosystem material requires contextual learning resources so that students can relate ecosystem concepts to environmental conditions in their surroundings. One local potential that can be utilized as a learning resource is the Kampar River in Koto Kampar Hulu District, Riau, which contains plankton communities as part of the biotic components of aquatic ecosystems. Data on plankton community structure can be integrated into ecosystem learning because it is related to biotic components, abiotic components, interactions among components, and the balance of aquatic ecosystems. This study aims to design and determine the validity of a biology handout on ecosystem material for Grade X senior high school students based on research findings on the plankton community structure in the Kampar River. This research is a handout development study using the ADDIE model, limited to the analysis, design, and development stages. The analysis stage was conducted through curriculum analysis, material analysis, and analysis of learning media needs. The design stage was carried out by preparing the format and content of the handout, while the development stage was conducted through product validation by a material expert, media expert, and biology practitioner. The designed handout contains ecosystem material based on local potential, plankton observation results, supporting images, practice questions, summaries, and references. Handout validation covered aspects of material structure, language, as well as format and graphics. The validation results showed that the handout obtained an average score of 3.80, categorized as highly valid. Therefore, the biology handout based on the plankton community structure in the Kampar River is feasible to be used as a contextual learning resource for ecosystem material in Grade X senior high school.